1992
DOI: 10.1111/j.1399-302x.1992.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of periapical infections in Egypt

Abstract: This study identifies and correlates proportions of bacteria in periapically involved anterior teeth of 85 adult Egyptian patients. Affected sites were free from caries and periodontal disease but had a history of trauma. The mean number of component bacterial species per specimen was 3.1. Anaerobic bacteria were the dominant flora present in specimen cultures, comprising 73% (190/259) of cultivable bacteria. The most frequently isolated organisms were Eubacterium species (68%), black-pigmented Bacteroides (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
(44 reference statements)
2
38
0
1
Order By: Relevance
“…Dark-pigmented anaerobic bacteria have been closely associated with acute symptoms of endodontic infections, including abscesses (41,47,(96)(97)(98)(99)(100). Two culture studies (42,101) found that virtually all abscesses of endodontic origin harbored one or more species of this group.…”
Section: Microbial Diversity In Acute Apical Abscessesmentioning
confidence: 99%
“…Dark-pigmented anaerobic bacteria have been closely associated with acute symptoms of endodontic infections, including abscesses (41,47,(96)(97)(98)(99)(100). Two culture studies (42,101) found that virtually all abscesses of endodontic origin harbored one or more species of this group.…”
Section: Microbial Diversity In Acute Apical Abscessesmentioning
confidence: 99%
“…was ranged from 17 to 81 percent of teeth studied. [4][5][6] In the sixteen samples that were positive for the presence of Eubacterium species, five samples were from patients who experienced preoperative pain and/or swelling. Statistical analysis did not reveal any significant associations between the bacterial presence or absence of Eubacterium spp.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…The organism Eubacterium lentum, which was recently reclassified as E. lenta had been identified in a number of endodontic studies by culturing. [4][5][6] This is a fecal organism that is uncommon in the oral cavity, and is difficult to distinguish from another closely related organism Eubacterium exiguum, recently reclassified as Slackia exigua, in that both organisms are generally not reactive to biochemical tests. 23,24) This latter organism has been identified in periodontal and endodontic infections.…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In fact interest in the micro-flora of root canals has largely been focused on anaerobic bacteria due to their predominance in untreated canals. 17,51,52 Enterococci, which are seldom found in these circumstances, have been isolated from teeth undergoing endodontic treatment and previously root treated teeth. [53][54][55][56] In a study of root filled teeth with apical periodontitis 69% of the bacterial strains recovered from the root canals were faculative anaerobes.…”
Section: Endodonticsmentioning
confidence: 99%